CLINICAL AND MORPHOLOGICAL CHARACTERISTICS OF THE CASE OF I NTRA-PULMONARY METASTASES OF BENIGN LEIOMYOMA - A. V. Reshetov; V. N. Klimenko; A. V. Elkin; L. B. Mitrofanova; I. V. Antonova; P. V. Konovalov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2019)
Uterine leiomyoma is rarely accompanied by the detection of distant metastases, including lungs. The basis of modern strategies of diagnosis of metastatic leiomyoma is the carrying out incisional or excisional biopsy of identified lesions with the subsequent performance of the immunohistochemical studies. Taking into account the indolent course of the disease, in modern practice, the main tactics of management of such patients is a long-term follow-up with the appointment of antiestrogen therapy.